Queen replacement in Mischocyttarus (Monocyttarus) cassununga (Hymenoptera, Vespidae, Mischocyttarini): A particular case - Murakami, A. S.N. [UNESP]; Shima, S. N. [UNESP] (My University, 2009)
The development of colonies of primitively eusocial wasps depends on intrinsic and extrinsic factors, namely social organization and climatic conditions. The present study was conducted to investigate how the process of replacement of the queen during the colonial cycle of Mischocyttarus cassununga takes place, and which are the determinant factors for its success. Our results showed that there are no disputes (fights) for hierarchical positions among other females after the disappearance of the queen. However, there is an increase on the overall frequency of aggressions, because of the efforts of the new queen (ex-2nd ranked female) in assuming control of the colony and affirming its reproductive dominance. Moreover, we recorded no alterations on the occupants of the hierarchical positions under the queen after its replacement, even in consecutive replacements in the same colony. We think that the climatic conditions, longevity of the queen, and the duration of the colonial cycle may be determinant during this process.
Keywords: Climatic conditions; Colonial cycle; Gerontocracy; Mischocyttarus; Neotropical species; Queen longevity